Keanekaragaman serangga yang terperangkap pada tumbuhan kantong semar (Nepenthes spp.: Nepenthaceae) di Gunung Samarinda, Aceh Barat Daya, Aceh, Indonesia: Diversity of insects trapped in pitcher plants (Nepenthes spp.: Nepentheceae) in Gunung Samarinda, Aceh Barat Daya, Aceh, Indonesia - Fitria, Restu; Atmowidi, Tri; Priawandiputra, Windra (Jurnal Entomologi Indonesia, 2025)
Pitcher plants Nepenthes spp. are insectivorous plants capable of trapping and digesting insects as an additional nutrient sources. Research on insects trapped in the pitchers of Nepenthes plants has been conducted in several regions of Indonesia. Unfortunately, similar research has never been reported in the Southwest Aceh region. This study aims to analyze the diversity and composition of insects trapped in the pitchers of Nepenthes plants in Gunung Samarinda Village, Southwest Aceh, Aceh, Indonesia. The research was conducted using the exploratory method with purposive sampling from January to July 2024, along the path leading to the oil palm plantation. Insect samples were collected from every Nepenthes plant found at the research location and were identified to the species level. The results showed that a total of 1,740 individuals, belonging to 18 species, 12 families, and 6 insect orders, were found in the Nepenthes pitchers. The three most dominant insect species were Aedes aegypti (Linnaeus) (36.21%), Tetramorium marginatum Forel (16.90%), and Anoplolepis gracilipes Smith (13.33%). The highest insect diversity was found in pitcher of  Nepenthes rafflesiana, followed by N. gracilis, and N. ampullaria. However, there was no significant difference in insect composition among the Nepenthes species. These findings indicate that Nepenthes spp. at the research site function as natural traps for insects, with a dominance of certain species. The presence of Nepenthes in its habitat can play a role in the ecosystem balance, particularly in the interaction between insectivorous plants and insect communities.